PENGARUH PERTUMBUHAN EKONOMI, PENDAPATAN ASLI DAERAH, RETRIBUSI DAERAH, PAJAK DAERAH, DANA ALOKASI UMUM, DAN DANA ALOKASI KHUSUS TERHADAP BELANJA MODAL (Studi Pada Kabupaten/Kota Provinsi Jawa Tengah Tahun 2011-2013) - Veroliana Putri Candra Pratiwi, 12.05.52.0211; Alfasadun, Alfasadun (Students' Journal of Accounting and Banking, 2016)
This study aims to examine the economic growth, regional revenue, Levies, Local Taxes, General Allocation Fund and Special Allocation Fund to the Capital Expenditure in the District / City of Central Java province Years 2011-2013. The data used is data Economic Growth, Local Revenue, Levies, Local Taxes, General Allocation Fund, Special Allocation Funds and Capital Expenditure on Regency / City Central Java Province. As many as 105 samples obtained data. The research data were then tested by multiple linear regression. The results of this study indicate that: Economic Growth significant positive effect on Capital Expenditure. Local Revenue has a positive influence on the Capital Expenditure. Retibusi area has a positive influence on the Capital Expenditure. Local Taxes and no significant positive effect on Capital Expenditure. General Allocation Fund has a positive influence on the Capital Expenditure. Special Allocation Fund and no significant positive effect on Capital Expenditure.   Keywords: Economic Growth, Local Revenue, Levies, Local Taxes, General Allocation Fund, Special Allocation Funds, Capital Expenditures